MARITAL RAPE AND THE LIMITS OF CRIMINAL LAW: A COMPARATIVE CRITIQUE OF LEGAL GAPS IN INDONESIA AND SINGAPORE - Angkawidjaja, Elizabeth Vania; Wijaya, Emilia Metta Karunia (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2025)
Marital rape is a crucial issue in Indonesia and Singapore, influenced by patriarchal culture and legal loopholes. This study aims to analyse the comparison of marital rape laws between the two countries, identifying significant differences in legal systems, definitions, and criminal sanctions. Unlike the Indonesian Criminal Code, which does not explicitly recognize marital rape, Singapore has reformed its laws through the Criminal Law Reform Act 2019 to criminalize such acts. This study finds that Singaporean law can contribute to Indonesia, particularly in terms of arrest procedures, victim protection systems, and the concept of consent. Using a normative-juridical approach with comparative methods, this study provides recommendations for the modernization of Indonesian law, emphasizing the need for more specific regulations and the establishment of special family courts to ensure better protection for victims.